An Unusual Case of Limited Gastric Linitis Plastica in a Nigerian - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Linitis plastica is considered to be one of the rarer types of gastric cancers. The involvement of only the fundus is the least common of the morphologic variants. This limited type is hardly ever documented among sub-Saharan African patients in scientific literatures. This case report presents one such unique case. Using unique attributes of this case’s presentation, this article reviews clinical, endoscopic and radiologic aspects of the diagnosis of this unusual malignant entity.